Perbandingan Kecepatan Fotosintesis Pada Tanaman Sawi Hijau (Brassica juncea) yang diberi Pupuk Organik dan Anorganik - Hasbiah, St; Farhatul Wahidah, Baiq (Jurusan Biologi UIN Alauddin Makassar, 2013)
This study was conducted to determine the comparison of photosynthetic rate between organic and inorganic plant with mustard greens (Brassica juncea) as sample. The experimental design was a randomized block design with 3 times respectively using compost for organic crops and NPK for inorganic crops. Doses used is 20 g / kg soil for both. The results showed an average increase of oxygen pressure in the light reactions of organic crops is 0.123 hPa/s whereas the inorganic plant is0.028 hPa / s. The average pressure of oxygen organic crops decreased to 0.104 hPa / s whereas the inorganic plant -0.037 hPa / s in the dark reaction. Analysis of the data in this study using the unpaired t test and the results showed a significant difference between the rate of photosynthesis in plants organic and inorganic.Keywords: dark reaction, inorganic plant, light reaction, organic plant, the rate of photosynthesis